Effect of GATA3 rs3824662 gene polymorphism in Han Chinese children with pre-B-cell acute lymphoblastic leukemia with 10 years follow-up - Chu, Xinran; Qian, Maoxiang; Yang, Jin; Wu, Dong; Gao, Jing; Cao, Lu; Fang, Fang; Pan, Jian; Zhang, Hui; Hu, Shaoyan (Frontiers in Pediatrics, 2023)
Purpose To evaluate the impact of GATA3 rs3824662on pre-B-cell acute lymphoblastic leukemia (pre-B-cell ALL) susceptibility and long-term prognosis in Han Chinese children with pre-B-ALL treated by CCLG-2008 protocol in Children's Hospital of Soochow. Methods A total 256 childhood pre-B-cell ALL patients treated with the CCLG-2008 protocol were enrolled in this study, and 174 healthy children were used as case control. The GATA3 rs3824662 genotyping was performed by PCR followed with sanger sequencing. The association of genotype with clinical characteristics, treatment response, adverse events, and the outcome were analyzed. Results The A allele frequency of GATA3 rs3824662 in patients with pre-B cell ALL was significantly higher than that in healthy children (OR=1.41, 95% CI=1.042-1.908; P=0.026). Among pre-B-cell ALL patients, the GATA3 rs3824662 AA genotype was associated with poor prednisolone response and high blast cells burden on day 15 during induction therapy (P=0.011 and 0.007, respectively). Meanwhile, patients with rs3824662 AA variant suffered more sepsis than those with CC/AC variants (P=0.031). No significant differences were found on the cumulative incidence of relapse, overall survival and disease-free survival between AA and CC+AC genotype. Conclusion GATA3 rs3824662 was associated with susceptibility to Han nationality Chinese children with pre-B-ALL and could be a possible risk factor for poor early treatment response and treatment-related sepsis.